The development of an operational management procedure for the South African west coast rock lobster fishery - Johnston, Susan Joy (Department of Biological Sciences, 2016)
This thesis considers the development of an operational management procedure (OMP) to provide scientific recommendations for commercial TAC for the South African west coast rock lobster (Jasus lalandii) fishery. This fishery has been under considerable stress in recent years as a result of overfishing and low somatic growth rates. Present catch levels, less than 2000 MT, are substantially smaller than levels recorded in the past. The present biomass (above 75mm carapace length) is estimated to be only six percent of the pristine level. At the start of this research, no long-term management strategy for the resource existed. Neither was there any robust, tested, scientific method available for setting the annual TAC for the fishery, which resulted in a time-consuming and unsatisfactory scientific debate each year in developing a series of ad hoc TAC recommendations. The work presented in this thesis is thus aimed at answering two important questions. i) Can an adequate mathematical model be developed as a basis to simulate the resource and its associated fishery? ii) Can a self-correcting robust OMP be developed for the resource? The first phase of this thesis is the development of a size-structured population model of the resource and the associated fishery. A size-structured model is necessary as lobsters are difficult to age and hence most of the data collected are on a size basis. Furthermore, important management issues, such as the legal minimum size which has changed over time, require a model able to take size-structure into account. This model is fitted to a wide range of data from the fishery, including CPUE (catch-per-unit-effort) and catch-at-size information, by maximising a likelihood function. The model is shown to fit reasonably well to all data, and to provide biologically plausible estimates for its six estimable parameters.